(untitled) (Community Based Medical Journal, 2014)
The present study provides further evidence that oral administration of peppermint and coriander extracts are having memory boosting and memory regaining effects. The present study was undertaken to compare memory boosting and regaining effects of oral administration of peppermint and coriander extracts in adult wistar rats. Here we investigate the influence of oral intake of peppermint and coriander extracts on behavioral task performance by using T-maze and radial arm maze and physiological measures relative to a milk control group. When coriandrum and peppermint groups are compared, the memory boosting and regaining effects of peppermint is significant in R-maze, whereas memory boosting and regaining effects of coriandrum is significant in T-maze. We conclude that oral administration of peppermint and coriander extracts are having memory boosting and memory regaining effects. Hence we recommend peppermint and coriander can be used as a remedy in the management of Alzheimer’s disease and we also recommend further research in this area by investigating compound metabolism to optimize quantification of memory performance following peppermint and coriander ingestion. CBMJ 2014 January: Vol. 03 No. 01 P: 13-19